Competence, Motivation on Performance of Nursing: The Mediating Effect of Satisfaction - Saryadi; Liss Dyah Dewi Arini (Proceeding of International Conference on Science, Health, And Technology, 2019)
This study examines the mediating effect of satisfaction on the performance of nursing on the links between competence dan motivation. Total of 60 respondents obtained in this research with a census. Analyzed data used the path analyzed with quality of data, t-test, F-test, coefficient determination and Sobel test. Furthermore, the result of this study show competence and motivation have a positive effect and significance on the performance of nursing direct and indirect through satisfaction. This study indicates that variable competence is the dominant effect on performance nursing.